(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to analyse the relationship between the perceived mental image and the promoted image of the Green Mountain region, and to reveal the extent of the correspondence or discrepancy between what is presented by the bodies and media involved in promoting tourism in the region and the image formed in the minds of local tourists. The study is based on the premise that the success of a tourist destination is not only linked to the scale or intensity of promotional activities, but also depends on the authenticity of the promotional message and its ability to convey the characteristics and elements that shape the tourist’s actual perception. Within this framework, the study seeks to identify the components of the promoted image of the region, measure the dimensions of the mental image perceived by local tourists, and then compare the two images to reveal the similarities, differences and the gap between them. The study adopts a descriptive-analytical approach through a field study of the opinions of a sample of local tourists using a questionnaire, whilst employing appropriate statistical methods to test hypotheses and measure relationships and differences between the study variables. The study derives its significance from its focus on the Green Mountain region as one of Libya’s regions rich in natural, environmental and historical assets, given the limited number of studies that have examined its tourism image from a comparative perspective combining both the promotional aspect and the aspect of tourists’ perceptions. The findings of the study are expected to provide a scientific basis for developing the region’s promotional discourse and messaging, and to bridge the gap between the image being promoted and that perceived by local tourists, thereby enhancing the effectiveness of tourism promotion and supporting sustainable tourism development in the region.